2019
DOI: 10.1007/s11657-019-0569-2
|View full text |Cite
|
Sign up to set email alerts
|

Imminent fracture risk assessments in the UK FLS setting: implications and challenges

Abstract: With the recognition that a sentinel fracture leads to a high imminent risk of fracture, we discuss the implications and challenges of using imminent fracture risk in the secondary fracture prevention setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
(52 reference statements)
1
22
0
3
Order By: Relevance
“…Our findings are supported by results of previous studies, where 18% of women ≥65 years and 11-12% of women ≥50 years sustained a second osteoporotic fracture within 2 years of an index fracture [21,36,37]. Studies examining fracture risk over time after an incident fracture have demonstrated a 2.7 to 5-fold higher fracture risk within 1-2 years post-fracture (ie, imminent risk) compared to 1.4 to 2-fold higher 10year risk [12,38].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are supported by results of previous studies, where 18% of women ≥65 years and 11-12% of women ≥50 years sustained a second osteoporotic fracture within 2 years of an index fracture [21,36,37]. Studies examining fracture risk over time after an incident fracture have demonstrated a 2.7 to 5-fold higher fracture risk within 1-2 years post-fracture (ie, imminent risk) compared to 1.4 to 2-fold higher 10year risk [12,38].…”
Section: Discussionsupporting
confidence: 90%
“…These events can occur in up to 23.2% of patients [70] and risk factors include recent fracture, fracture site, older age, osteoporosis and comorbidities, e.g., cognitive dysfunction, central nervous system polypharmacy, reduced physical activity, poorer general health as well as falls [71,72]. This supports the notion of early identification, assessment and treatment of those most at risk with the FLS model to reduce the future burden of fracture [73].…”
Section: Assessment Of Riskmentioning
confidence: 85%
“…For example, for patients in whom there is particular urgency to build BMD and quickly reduce fracture risk, a bone-forming agent may be prescribed prior to transitioning the patient to an antiresorptive therapy-an approach validated by the recent VERO and ARCH studies of teriparatide (Forteo, Eli Lilly, Indianapolis, IN) and romosozumab (Evenity, Amgen, Thousand Oaks, CA), respectively [34,35]. Roux and Briot [36] have offered a framework for understanding and using information on imminent risk in the routine care setting, and a 2019 paper by Pinedo-Villanueva et al [37] has recommended the assessment of imminent risk in the fracture liaison service (FLS) setting to identify the patients most in need of treatment with potent anti-osteoporosis medications with a rapid onset of action. Imminent risk assessment may also help clinicians tailor other patient support efforts, such as education on fall prevention and management of comorbidities and medications that may increase risk for fracture.…”
Section: Discussionmentioning
confidence: 99%